Epigenomic Regulation of Development and Regeneration in the Mammalian Retina - VandenBosch, Leah S (My University, 2020)
Diseases and damage to the retina lead to broad losses in retinal neurons and eventual visual impairment. Although the mammalian retina has no inherent regenerative capabilities, fish have robust regeneration from Müller glia (MG). Recently, the Reh lab has shown that driving expression of the proneural transcription factor, Ascl1 in adult mouse MG stimulates neurogenesis from these cells—in vitro and in vivo—similar to that which occurs in fish. The regeneration observed in the mouse is limited however, by the types of neurons that can be derived from the MG; Ascl1-expressing MG primarily generate bipolar cells. Additionally, Ascl1-based regeneration in the mouse retina is restricted temporally as the MG develop. To better understand the limits to mammalian MG reprogramming, I used RNA-seq and ATAC-seq to compare FACS purified cells. I firstly compared reprogramming treatment combinations in adult regeneration, as well as comparing highly neurogenic newborn mouse progenitors to developing MG. Additionally, I explored the epigenomic roles on fate decisions by comparing glial type cells to retinal neurons, and by modulating the epigenome with small molecule inhibitors ex vivo. I found that while there were many similarities between MG and progenitors, E-box regulatory regions lose accessibility as NFI binding domains increase in accessibility. Analysis of young glia reveals an intermediate epigenomic and transcriptomic profile that directs intermediate reprogrammability of glia as the young retina develops. Similarly, increasing reprogramming factors increased neurogenesis-related accessibility that relates directly to adult MG regeneration outcomes. Broader modifications to the epigenome can thus redirect fate decisions as MG redifferentiate ex vivo. Fate decisions do not appear to be directed, however, by inherent epigenomic similarity to retinal neurons, but instead by pioneering factor preference for binding sites. Overall, my analysis demonstrates the roles in which epigenomic accessibility reveals glial potential for neurogenesis during Ascl1-induced regenerative responses in mammalian retinas.
Thesis (Ph.D.)--University of Washington, 2019
Keywords: Development; Epigenetics; Glia; Regeneration; Retina; Neurosciences; Developmental biology; Molecular biology; Molecular and cellular biology